2015
DOI: 10.1007/s11051-015-3004-7
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured mesoporous silica: new perspectives for fighting antimicrobial resistance

Abstract: This paper investigates the antimicrobial potential of nanostructured mesoporous silica (NMS) functionalized with essential oils (EOs) and antibiotics (ATBs). The NMS networks were obtained by the basic procedure from cetyltrimethylammonium bromide and tetraethyl orthosilicate in the form of granules with diameters ranging from 100 to 300 nm with an average pore diameter of 2.2 nm, as confirmed by the BET-TEM analyses. The Salvia officinalis (SO) and Coriandrum sativum (CS) EOs and the streptomycin and neomyci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In our previous studies, we have also shown that a potential chemotherapeutic, the fungal derivative Ophiobolin A, underwent significantly less degradation when adsorbed to MSNPs [35]. Other studies have reported the use of nanostructured mesoporous silica loaded with essential oils against the planktonic form of the bacteria P. aeruginosa and Staphylococcus aureus [36] as well as against the fungus Aspergillus niger [37]. Different methods for essential oil loading into MSNPs have been reported.…”
Section: Discussionmentioning
confidence: 89%
“…In our previous studies, we have also shown that a potential chemotherapeutic, the fungal derivative Ophiobolin A, underwent significantly less degradation when adsorbed to MSNPs [35]. Other studies have reported the use of nanostructured mesoporous silica loaded with essential oils against the planktonic form of the bacteria P. aeruginosa and Staphylococcus aureus [36] as well as against the fungus Aspergillus niger [37]. Different methods for essential oil loading into MSNPs have been reported.…”
Section: Discussionmentioning
confidence: 89%